2002
DOI: 10.1097/00004691-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Proprioceptive Input on Parkinsonian Tremor

Abstract: Previous studies have shown a modification of parkinsonian tremor (PT) by proprioceptive input induced by passive joint movements. The authors investigated the impact of electrically evoked proprioceptive input on PT. In eight patients with PT they recorded surface EMG from the opponens pollicis muscle, and forearm extensors and flexors. Rhythmic electrical stimulation was applied to the ipsilateral median nerve at the wrist using a submaximal stimulus intensity and stimulus frequencies between two stimuli per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…In a few cases, this view was corroborated by coherence observations between such cerebral rhythms and tremor ( Zirh et al, 1998 ; Hurtado et al, 1999 ; Timmermann et al, 2003 ). Other investigations, however, obtained results strongly suggesting the involvement of proprioceptive input and peripheral loops or spinal motor systems in tremor generation ( Rack and Ross, 1986 ; Burne, 1987 ; Spiegel et al, 2002 ; Rivlin-Etzion et al, 2008 ). Although hypotheses assuming their supra-spinal origin are far more popular, the neural basis of PD tremor remains unclear.…”
Section: Introductionmentioning
confidence: 93%
“…In a few cases, this view was corroborated by coherence observations between such cerebral rhythms and tremor ( Zirh et al, 1998 ; Hurtado et al, 1999 ; Timmermann et al, 2003 ). Other investigations, however, obtained results strongly suggesting the involvement of proprioceptive input and peripheral loops or spinal motor systems in tremor generation ( Rack and Ross, 1986 ; Burne, 1987 ; Spiegel et al, 2002 ; Rivlin-Etzion et al, 2008 ). Although hypotheses assuming their supra-spinal origin are far more popular, the neural basis of PD tremor remains unclear.…”
Section: Introductionmentioning
confidence: 93%
“…Among the review articles, ten studies reported the effects of peripheral electrical stimulation results on patients with ET [18][19][20][21][22][23][24][25][26][27] while ten studies reported on patients with PD [28][29][30][31][32][33][34][35][36][37] and seven studies included both patients with ET and patients with PD [16,17,[38][39][40][41][42]. In order to compare electrical stimulation strategies, some studies also included healthy volunteers that either mimicked tremorgenic activity during experimentation or were subject to artificially induced tremors for experimentation [31,38,41].…”
Section: Target Populationsmentioning
confidence: 99%
“…These include the basal ganglia (Bergman & Deuschl, 2002; Liu et al 2002; Brown, 2003) and the thalamus (Lenz et al 1988). Other findings argue for the participation of proprioceptive input in this process (Rack & Ross, 1986; Spiegel et al 2002). There also exist observations suggesting the involvement of peripheral loops (Burne, 1987) and spinal motor systems (Rivlin‐Etzion et al 2008) in tremor generation.…”
Section: Introductionmentioning
confidence: 99%